Sound waves of progress: advancing endoscopic ultrasound in pediatric gastroenterology - Roy, Sumith; Gitter, Rachel; Nguyen, Jennifer; Huang, Andrew; Huang, Clifton (Frontiers in Pediatrics, 2025)
IntroductionA substantial body of research validates the application of endoscopic ultrasound in adults in the management of biliary and pancreatic conditions. There is limited data regarding its impact on children, although its use has steadily increased over the years. This study aims to assess long-term data on indications, efficacy and safety of endoscopic ultrasound in pediatric patients.MethodsThis ambispective registry data reflects a single-center experience of endoscopic ultrasound either as a stand-alone procedure, or in conjunction with guided interventions such as lumen-apposing metal stents or as a pre-assessment tool prior to other interventions such as endoscopic retrograde cholangiopancreatography, both of which were independently performed by a pediatric gastroenterologist.ResultsA total of 294 EUS were performed in 216 patients (55.1% female, median age (IQR) 15 [11.9–16.9] years). Technical success was 100% and no complications were associated with EUS.DiscussionThis robust dataset adds to the emerging evidence of EUS performed with a high technical success rate coupled with low risk for adverse events.